2015
DOI: 10.1186/s12914-015-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Childhood sexual abuse experiences and its associated factors among adolescent female high school students in Arbaminch town, Gammo Goffa zone, Southern Ethiopia: a mixed method study

Abstract: BackgroundChildhood sexual abuse is a major social problem in Africa including Ethiopia. Moreover, little has been explored about the pattern of childhood sexual abuse in the context of high school students in Ethiopia in general and in Arbaminch town in particular. Thus, the present study aims to assess the prevalence and associated factors of childhood sexual abuse among adolescent female high school students in Arbaminch town.MethodsA school- based, cross-sectional study was conducted among adolescent femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 15 publications
6
22
1
4
Order By: Relevance
“…Similarly, the highest perpetrators of sexual violence were boyfriend/girlfriend, teachers, and family members, accounting for 35.3%, 25.9% and 14.4% respectively. This nding is consistent with studies conducted among school students in Addis Ababa, Jimma, and Tanzania that reported greater number of respondents were perpetrated by someone they closely knew and the most common perpetrators were found to be friends, teachers, peers and close relatives (17)(18)(19)(20) .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, the highest perpetrators of sexual violence were boyfriend/girlfriend, teachers, and family members, accounting for 35.3%, 25.9% and 14.4% respectively. This nding is consistent with studies conducted among school students in Addis Ababa, Jimma, and Tanzania that reported greater number of respondents were perpetrated by someone they closely knew and the most common perpetrators were found to be friends, teachers, peers and close relatives (17)(18)(19)(20) .…”
Section: Discussionsupporting
confidence: 88%
“…However, lack of free discussion with parents and gender difference were strong predictors of violence elsewhere but not in our study. This might be due to paternalistic approach of child caring in Ethiopia considered as a norm for both sex (9,11,19) .…”
Section: Discussionmentioning
confidence: 99%
“…Living with mother only or father alone was 2 to 2.5 times more likely associated with violence compared to living with both parents. This finding was consistent with a study done in Goa, India [29] and Arbaminch town, Gammo Goffa zone, Southern Ethiopia [30]. The possible explanation could be, parental monitoring and supportiveness minimize their chance of exposure to risks of substance use and violence.…”
Section: 5%supporting
confidence: 92%
“…3 Psychological sequels, such as low self-esteem, anxiety, depression, anger, aggression, post-traumatic stress, sexual difficulties, suicidal thoughts, and low school performance, can be found in young adults with a history of sexual violence. 4 The violence suffered by children and adolescents can also have an impact on their families, on future relationships, and on the social environment in which they live.…”
Section: Introductionmentioning
confidence: 99%